Changes in soil fauna associated with litterfall decomposition in a cloud forest - VARELA, AMANDA; CORTÉS, CAMILO; COTES, CATALINA (Revista Colombiana de Entomología, 2007)
The functional diversity and role of soil fauna on litterfall decomposition were studied in a cloud forest located southwest of the Sabana de Bogota. A decomposition experiment was set up, confining 10 g of litterfall in mesh bags. A total of 24 bags was set out, half of which contained naphthalene to avoid the entry of soil fauna. At two, four and 12 months, four bags of the treated litterfall and four of the control were collected. Each bag was placed in a Tullgren funnel to extract the associated soil fauna. This was identified to the lowest taxonomic level possible and classified into functional groups. Richness and diversity were calculated using Shannon and Simpson indices. Litterfall was dried and weighed in order to calculate percent decomposition. in the litterfall treatment there was a reduction in the abundance or absence of soil fauna during the first 60 days due to naphthalene, but there was no difference in percent decomposition between the treatment and control. There was a greater abundance of detritivores, followed by litter transformers and phytophages over the three sampling periods. Richness, dominance and equitability of functional groups were not different between the litterfall treatment and the control. This suggests that the role of soil fauna in the decomposition of litterfall is less relevant in this forest than lowland forests.